Peningkatan Keamanan Sistem Informasi Melalui Klasifikasi Serangan Terhadap Sistem Informasi - Johan Ericka Wahyu Prakasa (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2020)
Nowadays, many information systems were developed to ease human life. This massive explosion of information systems attracts many attackers to get the valued data inside the information systems. There are many interesting data was held inside the information systems from personal ID Card number to bank accounts. That's why security must be involved in information systems development in the first place. This research study attacks to information systems and classified it into information system components. As a result, there are many attacks on every information system components. This research also gives advises to securing the information system from every information systems components.